Green Human Resource Management, Organizational Citizenship Behavior Towards the Environment, And Business Sustainability among Selected Construction Companies in Cebu City, Philippines - Flores, Jelissa; Delantar, Alexander Franco A.; Cabatingan, Albim Y. (Future Science / FSH-PH Publications, 2024)
This study investigated the correlation between Green Human Resource Management (GHRM), Organizational Citizenship Behavior towards the Environment (OCBE), and Business Sustainability among selected construction companies in Cebu City. The study utilized a descriptive-correlational-comparative approach with the participation of 102 heads and staff of selected construction companies in Cebu City. The selected statistical treatments showed a positive relationship among the three indicators, meaning they can significantly influence organizational performance and shape the organizational culture. Also, the study's findings revealed that behavior towards green practices is contingent upon the organization's commitment to the goals of GHRM and OCBE, which can affect business sustainability. With that in mind, the researchers have concluded that green human resource management practices have become a part of the organization's mindset. Both management and employees value GHRM indicators, reflected in their behavior towards the environment and business sustainability practices. Furthermore, the study recommends that the construction companies that participated in the research should adopt the sustainability framework created by the researchers.